Tratamento de água produzida através do processo de flotação utilizando a Moringa Oleífera Lam como coagulante natural. - Santana, Claudia Ramos (2009)
An oilfield lifecycle naturally exhibits a transition time when it becomes exhausted, since forward large water to oil ratios starts to be experienced, due to the proper conditions of oil reservoir or as a consequence of water injection with the purpose of oil secondary recovering. The development of new technologies for produced water treatment or the improvement of the existing ones is an issue of great importance to the petroleum industry development, minimizing environmental impacts. The flotation process has been extensively used to remove oil, mainly by dissolved air flotation (DAF) that consists of four basic steps: generation of bubbles in oily wastewater; contact between the gas bubbles and oil drops suspended in water; attachment of oil drops to gas bubbles; flotation of air-oil mixture to the surface where the oil is separated. In cases where the effluent needs coagulation, this step becomes an important point to any downstream processing technology. The use of environmentally correct coagulants represents an alternative way to the treatment of sewage and has demonstrated some advantages in relation to chemical coagulants, specifically due to its biodegradability, low toxicity and low surplus sludge production. This study proposes to evaluate the oil-water separation efficiency from produced water through DAF process by using Moringa oleifera Lam as a natural coagulant. Some tests were performed to characterize the oil and the Moringa s cake. Further, other experiments were performed to optimize the coagulation-flocculation process by changing the concentration of Moringa oleifera Lam in the range of 0.05 to 3.5 g/L, with samples of synthetic produced water (SPW) and real produced water (RPW) to get the optimum coagulant concentration in each sample and to determine its action on salted and unsalted emulsions, prepared, respectively, by adding or not NaCl. In the second stage, tests were also performed to optimize DAF process with RPW and SPW samples to evaluate the coagulant agent performance and to establish the kinetic modeling to estimate the separation efficiency. The optimal Moringa s concentration was 2.5 g/L for SPW samples and 1.5 g/L for RPW samples. The greatest DAF s efficiencies by using Moringa oleifera Lam were obtained when the recycling ratio (RR) were set to 40% and 60%, corresponding to oil removal efficiencies of 63.84 and 64.45 %, respectively, for SPW samples, and 55.28 and 59.63%, respectively, for RPW samples. In the case of SPW, the fit of an order one kinetic model provided k=0.03261s-1, showing satisfactory results compared to experimental data. For the case of RPW, the k value to a second-order kinetics model was 3.614x10-4 L.mg-1s-1, exhibiting weak correlation with the experimental results. The use of Moringa oleifera Lam as natural coagulant in the DAF process provided very good results, been considered an available alternative technique for produced water treatment.